MiR‐206 family is important for mitochondrial and muscle function, but not essential for myogenesis in vitro. Issue 6 (11th April 2020) - Przanowska, Roza K.; Sobierajska, Ewelina; Su, Zhangli; Jensen, Kate; Przanowski, Piotr; Nagdas, Sarbajeet; Kashatus, Jennifer A.; Kashatus, David F.; Bhatnagar, Sanchita; Lukens, John R.; Dutta, Anindya
Abstract: miR‐206, miR‐1a‐1, and miR‐1a‐2 are induced during differentiation of skeletal myoblasts and promote myogenesis in vitro. miR‐206 is required for skeletal muscle regeneration in vivo. Although this miRNA family is hypothesized to play an essential role in differentiation, a triple knock‐out (tKO) of the three genes has not been done to test this hypothesis. We report that tKO C2C12 myoblasts generated using CRISPR/Cas9 method differentiate despite the expected derepression of the miRNA targets. Surprisingly, their mitochondrial function is diminished. tKO mice demonstrate partial embryonic lethality, most likely due to the role of miR‐1a in cardiac muscle differentiation. Two tKO mice survive and grow normally to adulthood with smaller myofiber diameter, diminished physical performance, and an increase in PAX7 positive satellite cells. Thus, unlike other miRNAs important in other differentiation pathways, the miR‐206 family is not absolutely essential for myogenesis and is instead a modulator of optimal differentiation of skeletal myoblasts.